Analysis of anthelmintics market for ruminant animals in Ukraine - Kruchynenko, O.; Bondarevskyi, I. (Scientific Progress & Innovations, 2022)
The article provides data on the analysis of the market of anthelmintics for ruminants in Ukraine. According to modern literature data, there are currently more than 1500 antiparasitic drugs and their dosage forms in the world, which are used by specialists in daily veterinary practice. In livestock farms in Ukraine, drugs belonging to four chemical groups are used to treat helminthiasis of the gastrointestinal tract: benzimidazole, imidothiazole, macrocyclic lactones, and combined agents. The aim of the research was to establish the dependence of the cost of processing one head on the factors that can affect the price of drugs in Ukraine. Based on the results of the research, it was established that only 38 anthelmintics from different manufacturers were available from the proposed range of medicines for the treatment of cattle, sheep and goats for helminthiasis (October 2022). As a result of the conducted research, it was found that the highest percentage in Ukraine is occupied by anthelmintic drugs in the form of a solution (47.4 %). Single-component medicines for ruminants (57.9 %) prevail over multi-component ones (42.1 %). In the domestic pharmaceutical market, the absolute majority (81.6 %) is occupied by anthelmintics manufactured in Ukraine. The largest share of drugs in the pharmacy chain of Ukraine is made up of drugs of the LLC "Brovafarma" (23.7 %) and the company "Vetsintez" (18.4 %). Regression analysis is a widely used statistical technique for building a model from a set of data about two or more variables. Linear regression is based on linear correlation and assumes that a change in one variable is accompanied by a proportional change in another variable. However, multiple linear regression is more commonly used, which allows us to analyze more than one predictor or variable. As a result of the research, it was found that the coefficient of determination (R2) was 0.08 at the significance level of P<0.05. Since the contribution of the probable variable to the model does not exceed 8.0 %, it is unacceptable for use. The specified model does not include statistically significant predictors (purchase price of the active substance, production cost, etc.).